Towards Sustainable Management of Forests in India - Kotwal, P. C.; Chandurkar, Dharmendra (Indian Forester, 2003)
As part of the forestry principles, enumerated in the 1992 UNCED, governments agreed to pursue the formulation of scientifically sound criteria and guidelines for the management, conservation and sustainable development of all types of forests. Following the Rio Summit, countries took various initiatives to develop comprehensive guidelines for achieving the objectives of Sustainable Forest Management (SFM) and followed the approach of establishment of Criteria and Indicators (C&I). Criteria & Indicators in this regard were developed as an accepted framework for assessing sustainability of forest management systems and practices. Criteria constitute a set of key elements that define the scope of the concept of SFM. They reflect a series of broadly held societal values, the environmental, social and ecological benefits of forests that should be maintained for future generations. Indicators are chosen to provide measurable features of each criterion. Today, 140 countries are involved in nine major international processes for development of Criteria and Indicators for Sustainable Forest Management applicable to the specific ecological, environmental and socio-cultural conditions. In tune with the regional, international and national initiatives the Indian initiative, christened the Bhopal-India Process was taken by Indian Institute of Forest Management. The process is now recognised as the official Indian initiative for development of C&I for SFM in India. The process led to development of 8 criteria and 43 related indicators for SFM at national-level. This paper discusses the concepts of SFM and C&I. The evolution of Bhopal-India process and the progress achieved is also illustrated in the paper.